Analisis penerapan konsep critical thinking dalam pelajaran ipa selama pembelajaran daring kelas v sekolah dasar - Larmi Yulinawati; Siti Wahyuningsih; Suharno Suharno (Universitas Sebelas Maret, 2022)
The purpose of this study was to describe the application of the concept of critical thinking in science lessons during online learning for class V SD Muhammadiyah Jatiyoso. This research is important as a consideration regarding the determination of science learning policies. This is because of the importance of critical thinking skills in the 21st century. This research is a qualitative research with descriptive qualitative research methods. The subjects of this study were fifth grade teachers, and 6 fifth grade students at SD Muhammadiyah Jatiyoso for the 2020/2021 academic year. The results showed that the application of the concept of critical thinking in science lessons during online learning still could not be done optimally. Both from the point of view of teachers and students, the limitations in communicating the material are felt to be limited. In the application of Focus and Reason both students and teachers have been able to apply it well. However, the other ISC indicators have not been fulfilled properly, because students are guided more by their parents at home, so teachers are not able to provide direct feedback to students. The results of the Overview have been seen but are still not going well.